Integral Transforms of Pragathi-Satyanarayana’s \(I\)-function - Satyanarayana, B.; Kumar, D. K. Pavan; Kumar, Y. Pragathi; Srimannarayana, N. (Communications in Mathematics and Applications, 2025)
Many of the transformations like Euler, Hankel, Sumudu and \(K\)-transforms play a vital role in the field of engineering mathematics and have many applications. This paper refers to the study of Pragathi-Satyanarayana \(I\)-function of one variable. As a part of this study, we obtain different integral transforms of Pragathi-Satyanarayana \(I\)-function of one variable. Also, some of the generalized transforms have been obtained as special cases. The integral transformations developed here are useful in real-world applications of mathematical science.